Experimental evaluation of low-voltage DC/DC boost converters for renewable energy applications - Dawidziuk, Jakub; Harasimczuk, Michał; Kopacz, Rafał (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The demand for energy in the world is growing, and the requirements for the efficiency of energy-saving technologies used in renewable energy sources, especially prominent in terms of power electronics, are also increasing. In many renewable energy applications, high-efficiency, high-power DC/DC converters are necessary as an interface between various low-voltage sources and higher output voltage loads, e.g. in photovoltaics. The article presents a comprehensive study on reducing power losses in electric energy conversion in modified isolated and non-isolated DC/DC boost converters powered by low-voltage energy sources. The main desirable features, such as high energy efficiency, high conversion ratio, and low stress on the switches and diodes, were compared and further experimentally validated. The experimental evaluation indicates that the highest efficiency of 96.7%, with a conversion ratio of more than 10, was achieved in the interleaved boost-flyback DC/DC converter. Other investigated systems, namely non-isolated push-pull-boost converters, isolated half-bridge boost, and partially parallel boost converters, achieved slightly lower efficiency. Simultaneously, using the suggested topology, the passive component count was reduced. Furthermore, better utilization of switches and a higher conversion ratio are provided, as well as a possibility of working at a lower duty cycle compared to other step-up converter topologies. All in all, the proposed and studied converters exhibit certain advantages over other state-of-theart solutions and thus can be competitively and effectively employed in modern low-voltage DC/DC applications such as photovoltaics.